Video-Assisted Blended Learning on Cognitive Learning Outcomes of Junior High School Students on Waves and Sound Materials - Nita Rananda; Abdul Hakim; Muhammad Junus (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
This study aims to determine whether video-assisted blended learning influences the cognitive learning outcomes of junior high school students on wave and sound materials. This research is quantitative research. The method used in this study is pre-experimental designs with one group pretest-posttest. The sample in this study encompassed 31 students from class VIII-10 of SMP Negeri 4 Samarinda. Data collection uses a multiple-choice test consisting of 24 questions. The results showed that the use of video-assisted blended learning influences students’ cognitive learning outcomes. This was evidenced by the students’ experiencing an increase in cognitive knowledge learning outcomes during the 3-meeting learning. Here, the n-gain obtained from the means of the pretest and posttest was 0.61, which was more than 0.30 and less than 0.70. Therefore, it was concluded that the increase in the students’ learning outcomes was moderate.